2023
DOI: 10.1021/acsearthspacechem.3c00024
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of Formic and Acetic Acids to the Gas/Aerosol Interface

Abstract: Atmospheric aerosol particles are abundant and ubiquitous in both indoor and outdoor environments. Organic acid species in aerosols have an understudied effect on the environment and human well-being due to their unique interfacial properties. While it is widely accepted that the chemical and physical evolution of aerosol particles in the atmosphere is closely connected to interface-related phenomena, interface-specific methods suitable for investigating these topics in situ have only recently become available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This section outlines the experiments for SHS, ,, ESFS, and VSFS ,, from droplets in the air as well as the difficulty of the experiments which arises from using droplets in air instead of in an emulsion or a planar surface. Additional details can be found in the literature. ,,,,, …”
Section: Second-order Nonlinear Optical Scattering From Droplets In Airmentioning
confidence: 99%
“…This section outlines the experiments for SHS, ,, ESFS, and VSFS ,, from droplets in the air as well as the difficulty of the experiments which arises from using droplets in air instead of in an emulsion or a planar surface. Additional details can be found in the literature. ,,,,, …”
Section: Second-order Nonlinear Optical Scattering From Droplets In Airmentioning
confidence: 99%
“…SFG scattering (SFS) experiments have been successfully performed on suspensions and emulsions of water droplets in oil, , and thereby opened the door to studying small particles directly. The group of Yi Rao has worked on extending SFG scattering to free floating aqueous aerosol particles. While there has been some discussion about the experimental limitations involved in measuring SFS spectra of free floating aerosol, , such experiments would promise an insight not only into the role of the particle size and geometry but may also allow to extend studies to include much more realistic systems and introducing reagents into the gasphase. In a similar vein, it would be very interesting to study, for example, suspensions of mineral particles in a liquid, since it has been shown repeatedly that decreasing the particle size of solid materials can lead to quite surprising effects.…”
mentioning
confidence: 99%